The mermaid's purse - Polacco, Patricia (New York : G. P. Putnam's Sons, 2016)
"Stella loves books so much, she starts her own library--but then a storm threatens to destroy everything"-- Provided by publisher
Keywords: Books and reading -- Juvenile fiction